Teacher Morale and Professionalism: Study on Improving the Quality of Islamic Education - Zubairi Muzakki (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
Various efforts to improve the quality of education continue to be carried out by the government and the world of education that are in direct contact with subjects. Two things that become a benchmark for the effectiveness of science, namely, the morality and professionalism of teachers, are the primary keys to improving the quality of education. The culmination of an educational process in Indonesia is to produce human resources following national education goals. Therefore, four competencies must be mastered by a teacher in carrying out his profession. Teachers who have good morals will be role models for students. Meanwhile, professional competence becomes the teacher's reference in presenting quality learning. The morality and professionalism of good teachers in carrying out their profession is a must to improve the quality of education. Quality education will achieve the goals of national education and create human beings with noble character.